An Interventional Study Using Cell‐Mediated Immunity to Personalize Therapy for Cytomegalovirus Infection After Transplantation. Issue 9 (16th June 2017) - Kumar, D.; Mian, M.; Singer, L.; Humar, A.
Abstract : Cell‐mediated immune responses predict clinical cytomegalovirus (CMV) events but have not been adopted into routine practice due to lack of interventional studies. Our objective was to demonstrate the safety and feasibility of early discontinuation of antivirals based on the real‐time measurement of CMV‐specific cell‐mediated immunity (CMI) in patients with CMV viremia. Transplant patients were enrolled at the onset of CMV viremia requiring antiviral therapy. CD8 T cell responses were determined using the Quantiferon‐CMV assay, and results were used to guide subsequent management. A total of 27 patients (median viral load at onset 10 900 International Units/mL) were treated until viral load negative. At end of treatment, 14/27 (51.9%) had a positive CMV‐CMI response and had antivirals discontinued. The remaining 13/27 (48.1%) patients had a negative CMV‐CMI response and received 2 months of secondary antiviral prophylaxis. In those with a positive CMI and early discontinuation of antivirals, only a single patient experienced a low‐level asymptomatic recurrence. In contrast, recurrence was observed in 69.2% of CMI‐negative patients despite more prolonged antivirals (p = 0.001). In conclusion, this is the first study to demonstrate the feasibility and safety of real‐time CMV‐specific CMI assessment to guide changes to the management of CMV infection. Abstract : This study demonstrates the real‐time clinical utility of a cytomegalovirus cell‐mediated immunity assay to guide secondary antiviral prophylaxis in transplant recipients treated for CMV infection.